The Effect Of Contact Time Variations On The Efficiency Value And The Adsorption Kinetic Mechanism Of Iron (Fe) On Batik Waste Cual Using Chitosan - Widodo Budi Kurniawan; Herman Aldila; Livia Livia (Jurusan Fisika, Universitas Bangka Belitung, 2022)
English